2001
DOI: 10.1007/bf02864868
|View full text |Cite
|
Sign up to set email alerts
|

Application of tumor markers in ovarian malignancies

Abstract: Ovarian cancer is the fifth leading cause of death in women. The incidence of this malignancy increases in women over the age of 40. The overall five years survival is less than 30%, as most women present with advanced stage disease. Until recently, detection of early stage ovarian cancer has been difficult since it is usually nonpalpable and asymptomatic. The definitive diagnosis of an ovarian mass is a common problem in gynecologic patients with adnexal mass. The routine standard evaluation for adnexal masse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Myxoid areas in the gross were seen as cartilage microscopically and yellow areas were observed as adipose tissue, both were components of mesoderm. Incidence of the present study is 15% and comparable with theabove studies of Bhattacharya MM et al and Ganga S. Pilli et al [5,6] …”
Section: Mature Cystic Teratomasupporting
confidence: 92%
See 3 more Smart Citations
“…Myxoid areas in the gross were seen as cartilage microscopically and yellow areas were observed as adipose tissue, both were components of mesoderm. Incidence of the present study is 15% and comparable with theabove studies of Bhattacharya MM et al and Ganga S. Pilli et al [5,6] …”
Section: Mature Cystic Teratomasupporting
confidence: 92%
“…Out of 74 benign lesions, 69 lesions are unilateral (93.24%) and remaining 5 lesions are bilateral (6.75%). In 6 cases of malignant lesions 5 are unilateral lesions (83.33%) and bilateral are 1 lesion (16.67%) Ganga S. Pilli et al reported 92.2% of the benign lesions are unilateral and 74.2% of the malignant lesions are unilateral [6] which are correlated with the present study.…”
Section: Observationsupporting
confidence: 87%
See 2 more Smart Citations
“…Women with abdominal-pelvic masses constitute a challenging condition in general practice because the clinical features and findings from physical examination are usually nonspecific. The clinical application of tumor markers, such as serum concentration of CA 125, AFP and hCG is of great help not only as diagnostic aid but also in monitoring efficacy of any treatment modality like chemotherapy, radiotherapy or surgical resection [ 4 , 7 ]. Carbohydrate antigen 19-9 (CA 19-9) (a sialylated lewis glycoprotein antigen), a commonly used marker of benign and malignant hepatobiliary and pancreatic conditions, has also been found to be raised in some ovarian neoplasms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%